A guide to vitamins and their effects on diseases - OKTAY, NİHAL ŞEHKAR (Cambridge University Press, Cambridge (MA), USA, 2023)
This book provides a contemporary, comprehensive and general review of vitamins and the role of vitamins in diseases. In the first part of the book, readers will be informed about fat-soluble and water-soluble vitamins, vitamin-like substances, how they work in the body, their absorption, storage, transport, their recommended daily allowances, deficiencies and toxicity. In the second part, readers will discover how vitamins affect several diseases, and learn about their mechanism of action in diseases. The second part will also explore vitamin related minerals such as calcium, phosphorus, magnesium, potassium, copper and zinc. The book is unique in that it reveals the mechanism of action of each vitamin in relation to conditions such as the metabolism, autoimmune diseases, degenerative systems, infectious diseases, and aging. This book serves as a brief but beneficial guide for academic institutions, health professionals, practitioners, medical and dentistry students, nutritionists and pharmacists.
Keywords: Sağlık Bilimleri; Temel Bilimler; Health Sciences; Natural Sciences; Klinik Tıp (MED); Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; Clinical Medicine (MED); Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MULTIDISCIPLINARY SCIENCES; Multidisipliner; Multidisciplinary